2021
DOI: 10.1186/s13018-021-02427-0
|View full text |Cite
|
Sign up to set email alerts
|

Blocking circ-CNST suppresses malignant behaviors of osteosarcoma cells and inhibits glycolysis through circ-CNST-miR-578-LDHA/PDK1 ceRNA networks

Abstract: Background CircRNA CNST (circ-CNST) is a newly identified biomarker for prognosis of osteosarcoma (OS). However, its role in OS progression remains to be well documented. Methods Expression of circ-CNST, microRNA (miR)-578, lactate dehydrogenase A (LDHA), and pyruvate dehydrogenase kinase 1 (PDK1) was detected by quantitative real-time polymerase chain reaction and Western blotting. The physical interaction was confirmed by dual-luciferase reporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…A study unveiled that circSLC25A16 interacted with miR-488-3p/HIF-1a to activate LDHA by promoting its transcription in non-small-cell lung cancer (60). Likewise, circ-CNST/miR-578 and circATRNL1/miR-409-3P regulated LHDA in osteosarcoma (61,62). In pancreatic ductal adenocarcinoma (PDAC), circSLIT2 functioned as a miRNA sponge to target the miR-510-5p/c-Myc axis to activate the transcription by binding to the promoter region of LDHA (63).…”
Section: Noncoding Rnamentioning
confidence: 96%
“…A study unveiled that circSLC25A16 interacted with miR-488-3p/HIF-1a to activate LDHA by promoting its transcription in non-small-cell lung cancer (60). Likewise, circ-CNST/miR-578 and circATRNL1/miR-409-3P regulated LHDA in osteosarcoma (61,62). In pancreatic ductal adenocarcinoma (PDAC), circSLIT2 functioned as a miRNA sponge to target the miR-510-5p/c-Myc axis to activate the transcription by binding to the promoter region of LDHA (63).…”
Section: Noncoding Rnamentioning
confidence: 96%
“…A recent study has found that KDM6B promotes OS cell metastasis by regulating LDHA expression 61 . The knockdown of Circ‐CNST can antagonize the malignant behavior and glycolysis of OS cells by regulating the miR‐578‐LDHA/PDK1 axis 62 . Zhang et al.…”
Section: Glycolysis In Osteosarcomamentioning
confidence: 99%
“…61 The knockdown of Circ-CNST can antagonize the malignant behavior and glycolysis of OS cells by regulating the miR-578-LDHA/PDK1 axis. 62 Zhang et al found that CircATRNL1 enhanced glycolysis via the cir-cATRNL1/miR-409-3p/LDHA axis and promoted OS progression. 63 Other studies have found that non-coding RNAs: miR-323a-3p and miR-329-3p inhibit OS cell proliferation by targeting LDHA to repress OS glycolysis.…”
Section: Lactic Acid Productionmentioning
confidence: 99%
“… 70 The isozymes bind phosphates to specific serine residues present within the α-subunits of the E1 of the complex. 71 , 72 Hu et al 73 reported that Circ-CNST regulates PDK1 expression by sponging miR-578 and glucose consumption. Moreover, lactate production and ATP/ADP ratios were found to be suppressed in Circ-CNST upregulated osteosarcoma cells.…”
Section: Circrnas Regulate the Enzymes Regulatory Molecules And Oncogenes Involved In Glucose Metabolism In Cancermentioning
confidence: 99%